Effect of Different Doses of Sea Buckthorn (Hippophae rhamnoides L.) Seed Extract (Oil) on Histology of Islets of Langerhan of Pancreas in Alloxan Induced Diabetic Male Wistar Rats (Journal of Fatima Jinnah Medical University, 2025)
Background: Sea buckthorn seed oil extract contains saturated and unsaturated fatty acids. Alloxan monohydrate is oxygenated pyrimidine derivative, it produces diabetes in experimental animals. The objectives of this study was to determine the histological changes of sea buckthorn extract (seed oil) on Alloxan induced diabetic β-cells of pancreatic tissue in male Wistar rats.Method: 32 male Wistar rats were divided into 4 groups: A, B, C and D. Alloxan monohydrate in dose of 130mg/kg body weight was given as a single dose to experimental groups B, C and D. From each group half of the group the rats were sacrificed at day 4 of study and the rest on 25th day after administration of Sea buckthorn seed oil extract.Results: In comparison with the control group on the 4th day of the sacrifice all the rats in the experimental groups showed a decrease in diameter of islets of Langerhans, number of beta cells and an increase in number of beta cells pyknosis and vacuolization. On the 25th sacrificial day, only high dose Sea buckthorn (4ml) treated group D showed an increased in diameter of islets of Langerhans very close to that of controls while low dose (2ml) treated group C showed late recovery as compared to control group.Conclusion: The study assesses Sea buckthorn’s (seed oil) effects on serum glucose levels by using glucometer and histological parameters (diameter of islet, beta cell pyknosis, number of inflammatory cells) of islets of Langerhans of pancreas. It focuses on animal models, but human clinical trials are required to validate its efficacy and safety.
Keywords: Diabetes; Sea buckthorn seed oil; Alloxan monohydrate